A novel manufacturing process and validated predictive model for high-strength and low-residual stresses in extra-large 7xxx panels. (5th July 2019) - Zheng, Jing-Hua; Pan, Ran; Wimpory, Robert C.; Lin, Jianguo; Li, Chen; Davies, Catrin M.
Abstract: A novel manufacturing process, enabling the production of high quality (i.e. with low and controllable residual stress (RS) distributions and good mechanical properties) T-section 7xxx panels, has been established. This process provides a solution to residual stress induced distortion problems, which greatly concerns a range of industries, especially the aircraft industry. This process consists of three sequential steps — water quenching (WQ), cold rolling (CR) and constrained ageing (CA). The effectiveness of this process was experimentally verified through applying this process to laboratory sized 7050 T-section panels. The RS was measured by neutron diffraction and X-ray techniques, in addition to deflections and hardness at each processing stage. An integrated Finite Element (FE) model, including all three steps, was developed to simulate this manufacturing process and predict both the RS and the final strength distributions. It has been concluded that this novel process can effectively reduce the residual stresses from ±300 MPa to within ±100 MPa and produce T-section panels with required mechanical properties (i.e. hardness: 159 HV10 ). A cold rolling level of 1.5% was found most appropriate. The residual stress and yield strength distributions were accurately predicted by FE, providing a valuable prediction tool to process optimization for industrial applications. Graphical abstract: Unlabelled Image Highlights: A novel manufacturing process was developed to mitigate part distortion in T-section panels. Low and controllable residual stresses within 100 MPa were successfully achieved by the process. Integrated FE model, covering the entire process, was established and validated by the experimental data. Both residual stresses and the final yield strength distributions were accurately predicted. The suggested processing parameters are 1.5% cold rolling and 13 h constrained ageing.